Analisis Rasio Keuangan pada PT. Bank BCA, PT. Bank BNI, PT. Bank Mega, PT. Bank BRI di Indonesia Periode Tahun 2019-2023 - Diva Damai Maharani; Lea Berliana Jeni Salih; Yulita Alfonsia; Ataina Rusdya Fauziyah (Jurnal Mutiara Ilmu Akuntansi, 2024)
This study aims to analyze the financial performance of four major banks in Indonesia, namely PT Bank Central Asia (BCA), PT Bank Negara Indonesia (BNI), PT Bank Mega, and PT Bank Rakyat Indonesia (BRI), during the period 2019–2023. The analysis was conducted using financial ratios that include liquidity (current ratio, quick ratio), profitability (return on assets, return on equity), solvency (debt to equity ratio, debt to total asset ratio), efficiency (net interest margin), and market ratio (price to earnings ratio, dividend yield). This study uses a descriptive qualitative method with secondary data obtained from annual financial reports. The results of the study show significant differences in financial management among the banks analyzed. Bank BNI stands out in terms of liquidity, while Bank BRI excels in profitability and asset efficiency. Bank BCA shows good financial stability, while Bank Mega dominates in market attractiveness and dividend policy. However, each bank also faces challenges, such as low asset efficiency at Bank BNI, performance fluctuations at Bank BRI, and challenges in increasing profitability at Bank BCA.